MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIASIHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Rizal, Muhammad; Ramdani, Nasrul (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Islamic finance in general and Islamic banking in particular are very important matters for the attention of the Muslim community. This is because as religious people are required to carry out the rules that have been set and run them thoroughly both in worship, social, political and economic. however, it is still found that many of the Muslim community do not fully know about Islamic finance and institutions engaged in Islamic finance, especially banks. therefore it is necessary to socialize through community service programs regarding Islamic finance and Islamic banking. This community service is carried out in Ciasihan Village, Pamijahan District, Bogor Regency